Environmental Case Method in Learning Poetry of Students at Senior High School: An Ethnoecological Literature Study - Agustan Agustan; Juniaty Juniaty; Andi Bismawati; Masyitha Madani A T Syam (STAI Hubbulwathan Duri, 2024)
Literature and poetry play a crucial role in education by fostering students' sensitivity and reasoning towards literary works. This study aims to explore and describe practical approaches for teaching poetry using the environmental case method to students at SMA Negeri 1 Palu. This is a qualitative study, with data collected from class XI students during the 2022/2023 academic year through discussions and activities involving the case method. The descriptive qualitative method was employed to address two primary challenges: (1) students' difficulty in writing poetry and (2) students' difficulty in reading poetry. The findings reveal practical strategies to overcome these challenges by integrating environmental cases into the case method model. Specifically, this method helps students improve their poetry writing and reading skills by contextualizing poetry within real-world environmental issues. The implications of this research suggest that employing the environmental case method can enhance poetry teaching strategies broadly, making poetry more accessible and engaging for students. By applying this method, students can develop their poetry writing and reading abilities, thereby enriching their overall literary experience and appreciation.